Comparative Analysis of Neutrophil-to-Lymphocyte Ratio (NLR) in Typhoid Fever and Appendicitis Patients at Anutapura General Hospital, Palu - Nila Ardilla Arief; Mohamad Zulfikar; Israini Putri; Nur Fadilah Kudek (Journal of Innovative and Creativity, 2025)
The neutrophil-to-lymphocyte ratio (NLR) is a simple, rapid, and cost-effective hematological biomarker used to assess systemic inflammation. Typhoid fever and appendicitis are prevalent infectious diseases that cause acute inflammatory responses, yet comparative studies regarding NLR values between these two conditions are lacking. The study purpose was to analyze and compare the NLR values in patients with typhoid fever and appendicitis and to evaluate the clinical significance of these findings Materials and methods. This study employed a quantitative design with a cross-sectional approach at Anutapura General Hospital in Palu. Consecutive sampling was used, involving 54 typhoid fever patients and 57 appendicitis patients. Secondary data were analyzed using the Mann-Whitney and Chi-Square statistical tests. Results. Typhoid fever was most commonly observed in females (53.7%) and children aged 6-11 years (46.3%). Appendicitis predominantly affected males (54.4%) and late adolescents aged 18-25 years (80.7%). A normal NLR was found in 59.3% of typhoid patients, whereas 94.7% of appendicitis patients exhibited elevated NLR. The mean NLR in typhoid patients was 3.92, and most appendicitis patients had NLR values greater than 3. A statistically significant relationship was found between NLR and appendicitis (p = 0.039), but not with typhoid fever (p=0.076). Conclusions. NLR elevation is more pronounced and statistically significant in appendicitis than in typhoid fever, suggesting its stronger role as an inflammatory indicator for appendicitis. NLR can be considered a supportive tool in the early differentation of typhoid fever and appendicitis in acute abdominal cases.